Manajemen Produksi dan Pemeliharan Kebun Kepala Sawit Rakyat - Esro Paldanta (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Smallholder plantations account for a significant portion of Indonesia's total oil palm area, yet they consistently face a substantial yield gap compared to industrial estates. This study aims to evaluate the implementation of production management and technical maintenance in smallholder plantations and analyze the influence of management variables on Fresh Fruit Bunch (FFB) productivity. The research was conducted using a descriptive-quantitative approach with a survey method involving 80 respondents selected through proportionate stratified random sampling. Data were analyzed using correlation and simple linear regression to determine the relationship between maintenance intensity and yield. The findings reveal that the implementation of technical culture standards—including fertilization, weed control, and pruning—among smallholders averages only 53% of the ideal standard. A critical discovery is that 55% of farmers still utilize uncertified seeds, which significantly limits their long-term production potential. Statistical analysis demonstrates that Seed Quality (r = 0.82) and Fertilization Dosage (r = 0.78) are the most dominant variables influencing productivity. Farmers utilizing certified seeds achieved 18–22 tons/ha/year, while those using uncertified seeds only produced 8–11 tons/ha/year under similar conditions. This study concludes that poor production management is primarily driven by financial constraints and limited access to technical information. Strengthening farmer institutions and facilitating access to high-quality inputs are essential to bridging the yield gap and ensuring the economic sustainability of smallholder oil palm agribusiness